Chronic migraine caused a higher rate of tendency to cannabinoid agonist compared to morphine : Tendency to use cannabis in chronic Migraine - Mansoori, Mojdeh; Zarei, Mohammad Reza; Chamani, Goli; Nazeri, Masoud; Mohammadi, Fatemeh; Alavi, Samane Sadat; Shabani, Mohammad (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Opioid and cannabinoid systems have considerable roles in modulation of chronic pain as well as regulation reward circuit and addiction responses. This study investigated the effect of nitroglycerin (NTG)-induced migraine attack on the acquisition of morphine and cannabinoid-induced conditioned place preference (CPP) in male rats. Methods: Adult male rats (230-250 gr) were used. Experimental groups were included (n=10): control, opioid receptor agonist morphine (10mg/kg), WIN55,212-2 (1mg/kg) as a cannabinoid receptor agonist, NTG + morphine (10mg/kg) and NTG + WIN55,212-2 (1mg/kg). Nitroglycerin (10 mg/kg) was used to induce migraine attack every other day for 9 days. After migraine induction, conditioning performance was assessed by CPP test. During conditioning days, morphine and WIN55,212-2 were injected subcutaneously and intraperitoneally, respectively. Anxiety and locomotor activity were evaluated using open field test (OFT). Results: According to data, conditioning score for morphine-treated rats was significantly decreased following NTG-induced migraine. However, NTG-induced migraine was able to increase the conditioning score in WIN55,212-2 as compared to control group. In OFT, there were no significant differences in locomotor activity and grooming behaviors between experimental groups. However, time spent in the center of OFT box was significantly decreased in NTG plus morphine-treated rats as compared to control. Moreover, rearing response in NTG-treated groups which received either morphine or WIN55,212-2 decreased as compared to control group. Conclusion: NTG induced migraine prompts a decrease in morphine and an increase in cannabinoid performances. So, these compounds effects on drug dependency during migraine attack may occur at different mechanism or mechanisms.